Answer:
k= -11
Step-by-step explanation:
Let's simplify step-by-step.
7k−2(3k+1)−9
Distribute:
=7k+(−2)(3k)+(−2)(1)+−9
=7k+−6k+−2+−9
Combine Like Terms:
=7k+−6k+−2+−9
=(7k+−6k)+(−2+−9)
=k + −11
Answer:
okay so -2 and -12 should be next to each outher and 2 and 12 should be next to eachouthr
Step-by-step explanation:
The answer is <span>SAS (side, angle, side) SAS stands for "side, angle, side" and means that we have two </span>triangles<span> where we </span>know<span> two sides and the included angle are equal. If two sides and the included angle of one </span>triangle<span> are equal to the corresponding sides and angle of another </span>triangle, thetriangles<span> are </span>congruent<span>.</span>
|2x+3|-1<4
|2x+3|<5
1) when 2x +3 is positive
2x+3<5
2x<2
x<1 (-∞, 1)
2) when 2x+3 is negative
-(2x+3)<5
-2x-3<5
-2x<8
x>-4 (-4, ∞)
(-∞, 1)∩(-4, ∞)=(-4,1)
Answer:
can u zoom in and take picture
Step-by-step explanation: